PENGEMBANGAN E-MODUL BERBASIS MODEL GUIDED INQUIRY LEARNING PADA MATA PELAJARAN IPS KELAS VII SMP: Penelitian Pengembangan - Mayang, Fidia; Ulfia Rahmi; Fetri Yeni; Nofri Hendri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study was motivated by several facts found in the field. Students lack understanding of the material presented by teachers because the material is quite difficult to understand. This is due to the limited teaching materials used in social studies learning activities, which are not very interesting to students. There is also a limitation in the use of interactive teaching materials that can improve students' independent learning activities. In order to overcome these problems, E-Module teaching materials were developed to help make learning more interesting and to help improve students' understanding and willingness to learn independently. This study aims to produce a valid, practical, and effective E-Module for Grade VII social studies on Theme 4, “Turning Diversity into Strength,” to be used in the learning process.This research is a type of Research and Development (R&D). The model used in this development research is the Plomp development model. There are three stages in the Plomp development model, namely preliminary research (initial investigation), by conducting a needs analysis, prototype phase, by designing the social studies e-module product until it is valid and practical, and assessment phase, by testing its effectiveness. The validity test was conducted by three experts. The practicality test consisted of three stages, namely one-to-one evaluation, small group, and large class practicality. The effectiveness test was conducted in the seventh grade at Pertiwi Siteba Private Junior High School. The data type was primary data. The data collection instruments consisted of interviews, field observations, documentation, product validation questionnaires, student practicality questionnaires, educational practicality questionnaires, and multiple-choice test questions. The data analysis technique used descriptive analysis. The results of this study show product validation from subject matter experts with a percentage of 4.28 in the “highly valid” category, validation from media experts with a percentage of 4.85 in the “highly valid” category, student response questionnaires in the one-to-one evaluation with a percentage of 94.2% in the “highly feasible” category, small group evaluation with a percentage of 92.7% in the “Very Appropriate” category, and the results of the field test practicality with a percentage of 94.3% in the “Very Appropriate” category and the results of the assessment phase with a percentage of 78.26% in the “Good” category. The conclusion of this study is that the E-Module for Social Studies Based on the Guided Inquiry Learning Model for Grade VII Junior High School Social Studies is valid, practical, and effective for use in learning activities.